2005
DOI: 10.1002/ps.1056
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory‐based comparison of a molluscicide and an alternative food source (red clover) as means of reducing slug damage to winter wheat

Abstract: Slugs are major pests of many crops in the UK, including winter wheat, yet current methods of control are often unreliable. This study investigates the potential use of red clover, as an alternative food source, to reduce the amount of damage caused to winter wheat by the field slug, Deroceras reticulatum (Müller). Two laboratory-based studies, each conducted over a 7-day period, investigated the effects of red clover seedlings and commercial metaldehyde pellets on damage to winter wheat seeds and seedlings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Further, more biomass and residue cover can improve weed suppression (Mischler et al, 2010;Finney et al, 2016), reduce nutrient leaching from the system (Alonso-Ayuso et al, 2014;Farsad et al, 2011;Finney et al, 2016), and extend the time for N 2 fixation by leguminous CCs (Cook et al, 2010;Wagger, 1989;Ketterings et al, 2015). More CC biomass may also provide habitat for beneficial arthropods (Finke and Denno, 2002) including slug predators, potentially providing slug predator suppression, while the living CC may provide alternative food for slugs, further reducing slug damage of main crops (Brooks et al, 2005;Le Gall and Tooker, 2017). Growers have been increasingly interested in using PG to maximize these ecosystem services, but there are few published studies that quantify the impacts of the practice on which to base management recommendations for corn and soybean in the region.…”
mentioning
confidence: 99%
“…Further, more biomass and residue cover can improve weed suppression (Mischler et al, 2010;Finney et al, 2016), reduce nutrient leaching from the system (Alonso-Ayuso et al, 2014;Farsad et al, 2011;Finney et al, 2016), and extend the time for N 2 fixation by leguminous CCs (Cook et al, 2010;Wagger, 1989;Ketterings et al, 2015). More CC biomass may also provide habitat for beneficial arthropods (Finke and Denno, 2002) including slug predators, potentially providing slug predator suppression, while the living CC may provide alternative food for slugs, further reducing slug damage of main crops (Brooks et al, 2005;Le Gall and Tooker, 2017). Growers have been increasingly interested in using PG to maximize these ecosystem services, but there are few published studies that quantify the impacts of the practice on which to base management recommendations for corn and soybean in the region.…”
mentioning
confidence: 99%
“…In order for a slug control strategy that uses an alternative food to successfully reduce damage to wheat, previous laboratory findings must be replicable in a field situation 25. The field results showed that high populations of red clover gave up to 99% protection to wheat seeds, even at high slug densities, and that wheat seeds and seedlings gained as much as 55% more protection compared with the control (wheat only).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, red clover continued to be more palatable to slugs than did wheat over an extended 11 day test. In a follow‐on study an assessment of the ability of red clover to offer protection to vulnerable wheat crops, in comparison with the most commonly used method of slug control, metaldehyde, found that red clover was less effective in reducing damage to wheat seeds but equally as effective as metaldehyde in reducing damage to seedlings 25. Furthermore, both red clover and metaldehyde resulted in as much as 55% more protection to wheat seeds and seedlings then the wheat‐only control.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, practices based on non-inversion tillage have been shown to increase weed infestation and to modify the biological community of the soil [16]. In conservation agricultural systems, slugs can use weeds as an alternative food source, as is also true for to the plants seeded for intercropping [17][18][19][20]. In addition, the presence of crop residues on the soil surface may provide a suitable habitat for these pests [13,21], increasing their feeding activity [22].…”
Section: Introductionmentioning
confidence: 99%
“…In conservation agricultural systems, slugs can use weeds as an alternative food source, as is also true for to the plants seeded for intercropping [ 17 , 18 , 19 , 20 ]. In addition, the presence of crop residues on the soil surface may provide a suitable habitat for these pests [ 13 , 21 ], increasing their feeding activity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%